LC-MS/MS-based metabolomic study provides insights into altitude-dependent variations in flavonoid profiles of strawberries - Muhammad Junaid Rao; Muhammad Junaid Rao; Huaizheng Wang; Huaming Lei; Hongcha Zhang; Xiande Duan; Liuyuan Bao; Chengcui Yang; Duo Han; Yongzhi Zhang; Shunqiang Yang; Mingzheng Duan (Frontiers in Plant Science)
Environmental conditions significantly influence the metabolic composition and quality attributes of fruits. This study investigated the impact of altitude-associated environmental variation on flavonoid profiles and fruit quality parameters by comparing the “Red Face” strawberry variety grown in two distinct locations: high-altitude-associated environmental conditions in Zhaotong and low-altitude conditions in Dandong. Using LC-MS/MS analysis, we identified 163 bioactive flavonoids, comprising 85 flavonols, 37 flavanones, 33 flavones, and 8 flavanonols. The high-altitude environment of Zhaotong significantly enhanced specific flavonoid compounds, with notable increases in neohesperidin (20.4-fold), tamarixetin-3-O-glucoside-7-O-rhamnoside (17.7-fold), isovitexin (9.1-fold), and hesperidin (8.5-fold) compared to Dandong-grown fruits. Conversely, Dandong-grown fruits showed higher levels of chrysoeriol-7-O-glucoside (53.9-fold), 6-hydroxykaempferol-6,7-O-diglucoside (36.3-fold), and eucalyptin (9.7-fold). The tricetin 3’-glucuronide (24.49% vs 15.31%) and quercetin-4’-O-glucuronide (24.15% vs 15.59%), are the major flavonoids identified in Zhaotong strawberries than Dandong-grown fruits. Furthermore, strawberries cultivated in Zhaotong demonstrated superior antioxidant activities and capacity, increased quality parameters, including higher sugar content (15.30°Brix vs 10.96°Brix), increased ascorbic acid (15.73 mg/g vs 8.53 mg/g), and optimal firmness (20.51 N vs 23.16 N) than Dandong strawberries. These findings suggest that high-altitude cultivation conditions positively influence strawberry fruit characteristics, enhancing both bioactive compound profiles and overall fruit quality. This research provides valuable insights for optimizing strawberry cultivation conditions to maximize nutritional and commercial value.